1972
DOI: 10.1021/jf60182a013
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the exudate from cooked shell eggs

Abstract: Boiled and peeled eggs stored in Cryovac bags at 5°C produced a greenish-yellow fluorescent exudate.The amount of exudate increased from 1.26% at 1 day to 2.7% at 7 days, with no further increase on storage. The freeze-dried exudate contained 61 % protein, 21.25% carbohydrate, and 8.9% minerals.Chromatography of the exudate on Sephadex G-50 produced five fractions. The first two fractions, based on biological activity and chemical analysis, appeared to be ovomucoid-like. Fractions 3 and 4 contained large amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1973
1973
1973
1973

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Earlier it was shown that the exudate was rich in protein, namely ovomucoid (Nath et al, 1972). From the present data, it is clear that albumen dialyzate is rich in carbohydrate and low in protein.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Earlier it was shown that the exudate was rich in protein, namely ovomucoid (Nath et al, 1972). From the present data, it is clear that albumen dialyzate is rich in carbohydrate and low in protein.…”
Section: Discussionsupporting
confidence: 60%
“…Exudate was prepared as described earlier (Nath et al, 1972) and a 2% solution was dialyzed against distilled water. The dialyzate was either concentrated on a rotary evaporator or used directly for spectral analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation is also supported by the growth curve obtained with albumen with added egg exudate. The exudate is proteinaceous and rich in carbohydrate and also contains some riboflavin (13).…”
Section: Discussionmentioning
confidence: 99%
“…Egg exudate. Cooked egg exudate was prepared and freeze-dried as described by Nath et al (13). Eggs that are cooked, peeled, and packaged in Cryovac bags give out a greenish-yellow liquid.…”
Section: Methodsmentioning
confidence: 99%